Situational variations in request and apology realization strategies among international postgraduate students at Malaysian universities - Muthusamy, Paramasivam; Farashaiyan, Atieh (Canadian Center of Science and Education, 2016)
The present study attempted to describe the request, apology, and request mitigation strategies utilized by international postgraduate students in confronting different situations. In addition, it examined the effects of the situational factors of social distance, power, and imposition on the students’ choice of request and apology strategies as well as the modifications in requests. Another objective has been to categorize the difficulties students face in the production of the speech acts. One hundred and thirty international postgraduate students majoring in different fields voluntarily participated in this study. A Written Discourse Completion Task Questionnaire (Liu, 2005) and semi-structured interview were utilized for data collection procedure. The results of the questionnaire illustrated that the participants made use of IFID strategy for apologies and conventionally indirect expressions (Preparatory questions) for requests more frequently than other strategies. Moreover, the situational factors of social distance, power and imposition did not affect the participants’ choice of request and apology strategies but they had some influences on the use of mitigating strategies in different situations. Regarding modifiers, the students opted out external modifications (66.6%) more than internal modifiers (33.3%). Among the external mitigation types, “please” with 21% and grounders with 25% respectively have been utilized more than other external mitigation types. Finally, the results of the interviews indicated that the difficulties that students face in the production of the speech acts were grammar, expression, vocabulary and structure. This study has some implications for second language acquisition research and intercultural communication.